Upaya Kepemimpinan Kepala Sekolah dalam Meningkatkan Kualitas Sumber Daya Manusia (SDM) di Sekolah Dasar Muhammadiyah Terpadu Masaran Sragen Tahun Pelajaran 2015/2016 - Latif, Muhammad Nur, Drs. Ma'ruf, MM (2016)
The purpose of the study was to describe the efforts of headmaster leadership in improving HR, the problems in improving human resource development and the solutions overcome them. The research was a qualitative research with descriptive approach. The subjects were school principal, teachers and employees. The data collection techniques using interviews, observations and documentations, which was then analyzed using qualitative descriptive method. The results of this study proved that the efforts of headmaster leadership was effective in improving HR with the three characteristics of leadership styles. The efforts in improving human resources is through KKG, lectures, discussions, training and salaries and reward.the problems were 1) the difficulty of coordination between headmaster and the same age teachers, the school held a meeting solution and individual approach in particular;2) lack of direction and supervision, the solution is to do a personal approach and provide oversight on a regular basis through classroom visits;3) pluralistic society problem, the solution was to improve the communication betwen the committe of school, principals, teachers and employees improve communication with citizens.